Carbon Nitride Nanostructures for Sustainable Energy Production and Environmental Remediation - Eid, Kamel Abdelmoniem Mohamed (ISSN., 2021)
This book covers recent advances in the rational design and characterization of gCN nanostructures for energy and environmental remediation.